Transformations art and the city - Grierson, Elizabeth (Intellect, 2017)
The contributors explore the interactions between people and their urban surroundings through site-specific art and creative practices, tracing the ways in which people inhabit, imagine, and shape their cities. Drawing on the work of global artists, from Cambodia to Australia, New Zealand to the United States, this collection investigates the politics and democratization of space through an examination of art, education, justice, and the role of the citizen in the city. The essays explore how creative practices can work in tandem with ever-changing urban technologies and ecologies to both disrupt and shape urban public spaces
Keywords: Stadt; Kunst; Öffentlicher Raum; Urban beautification; Site-specific art; Public art; Art and society; Aufsatzsammlung